Bastion - King, Stephen, 1947-; Lipski, Robert (Poznan : Zysk i S-ka Wydawnictwo, 2000)
Polish translation of "The Stand". A horror tale by Stephen King about biological warfare researches.
Keywords: Biological warfare -- Research -- Fiction